1999
DOI: 10.1046/j.1365-2923.1999.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

A Delphi technique to identify and evaluate criteria for construction of PBL problems

Abstract: Judges from a school just having implemented PBL, found that Reasoning and Autonomy are the most important criteria for constructing PBL problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 13 publications
0
22
0
4
Order By: Relevance
“…Another possibility could be that the objectives and implementation of PBL curricula in Rouen University and the Polytechnic in this study are different (Des Marchais, 1999). While Des Marchais's (1999) study was conducted in a medical university, the present study was conducted in a polytechnic, which employs PBL across all modules.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Another possibility could be that the objectives and implementation of PBL curricula in Rouen University and the Polytechnic in this study are different (Des Marchais, 1999). While Des Marchais's (1999) study was conducted in a medical university, the present study was conducted in a polytechnic, which employs PBL across all modules.…”
Section: Discussionmentioning
confidence: 93%
“…Text analysis of their responses, based on semantic similarities, resulted in the identification of eleven problem characteristics. (Des Marchais, 1999;Dolmans et al, 1997;Shaw, 1976) showed that the students identified similar characteristics. Table 3 presents a comparison of students' perspectives from this study with other empirical studies (e.g., Des Marchais, 1999), and theoretical guidelines (e.g., Dolmans et al, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…14 This technique has successfully yielded assessment criteria for professional behaviors, 15 problem-based learning, 16 and procedural skills 17 in the health professions education context. Since assessment of CR in the OMPT certification process is a phenomenon of interest with broad applications in all 22 IFOMPT MO, the modified Delphi approach enabled us to access the opinions of a geographically diverse group of OMPT experts relevant to our study purpose.…”
Section: Methodsmentioning
confidence: 99%
“…Variations on the Delphi method have been reported-increasing the rounds from 2 to 5 and varying the number of participants in each round [9]. The size of groups in the Delphi method ranges from 7 to 350 people [10]; however, the most effective expert panel size is 10 to 15 members [11].…”
mentioning
confidence: 99%